Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/mcg.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Inpatient Split-dose Bowel Preparation System Improves Colonoscopy Quality and Reduces Repeat Procedures

Abstract: Our interdisciplinary initiative targeting inpatient colonoscopy preparations significantly improved quality and reduced repeat procedures, and hospital days. Other institutions should consider utilizing this framework to improve inpatient colonoscopy value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The detailed selection process is depicted on Figure 1. Eight randomized controlled trials (RCT) [15, 17, 1921, 23, 26, 27] and nine observational cohort studies [1114, 16, 18, 22, 24, 25] were available for analysis. In this systematic review, we classified included studies per intervention used for improving bowel cleanliness as follows: (1) education of patients and/or personnel regarding bowel preparation [1116], (2) modification of preparation regimens [1726], and (3) other interventions [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The detailed selection process is depicted on Figure 1. Eight randomized controlled trials (RCT) [15, 17, 1921, 23, 26, 27] and nine observational cohort studies [1114, 16, 18, 22, 24, 25] were available for analysis. In this systematic review, we classified included studies per intervention used for improving bowel cleanliness as follows: (1) education of patients and/or personnel regarding bowel preparation [1116], (2) modification of preparation regimens [1726], and (3) other interventions [27].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 illustrates the main characteristics of the included studies, published between 2003 and 2018, enrolling 2733 inpatients. All but one [20] were monocentric; fourteen [1113, 1517, 1923, 2527] and 3 [14, 18, 24] were prospective and retrospective studies, respectively. Among the prospective studies, 8 [13, 15, 17, 1921, 23, 26] randomized participants in 2 groups (intervention vs. control).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 In a quasi-experimental design, Yadlapati et al found that an automated split-dose bowel preparation resulted in decreased IBP, fewer repeated procedures, shorter LOS, and lower hospital cost. 18 Our study adds to these tools by identifying three additional risk factors which could be optimized for inpatients. Because our findings are observational, they should be subjected to prospective trials.…”
Section: Discussionmentioning
confidence: 99%